The Museum Istiqlal The Case of an Indonesian Islamic Museum - Zilberg, Jonathan (SUHUF, 2011)
This article describes the conflicted genesis of the Museum Istiqlal, the history of the creation of the collection, and the state of the institution relative to other Indonesian museums. It emphasizes both positive developments underway and the historical problems facing the institution. Above all, it focuses on the role the museum was originally intended to serve for the Indonesian Muslim public sphere and the significant potential the museum has to better serve that mission in the national and international sphere. In short, the article emphasizes that in the context of the Government of Indonesia’s current four year plan to revive the museum sector, the problems and opportunities presented at the Museum Istiqlal are symptomatic of endemic national challenges for both the museum and the education sector.